Synthesis and Biological Evaluation of 5-Fluoro-2-Oxindole Derivatives as Potential α-Glucosidase Inhibitors - Lin, Jing; Liang, Qi-Ming; Ye, Yuan-Na; Xiao, Di; Lu, Li; Li, Meng-Yue; Li, Jian-Ping; Zhang, Yu-Fei; Xiong, Zhuang; Feng, Na; Li, Chen (Frontiers in Chemistry, 2022)
α-Glucosidase inhibitors are known to prevent the digestion of carbohydrates and reduce the impact of carbohydrates on blood glucose. To develop novel α-glucosidase inhibitors, a series of 5-fluoro-2-oxindole derivatives (3a ~ 3v) were synthesized, and their α-glucosidase inhibitory activities were investigated. Biological assessment results showed that most synthesized compounds presented potential inhibition on α-glucosidase. Among them, compound 3d, 3f, and 3i exhibited the most potent inhibitory activity with IC50 of 56.87±0.42 μM, 49.89±1.16 μM, 35.83±0.98 μM, respectively, which were about 10 ~ 15 folds higher than acarbose (IC50 = 569.43±43.72 μM). Kinetic mechanism study revealed that compound 3d, 3f, and 3i inhibited the α-glucosidase in a reversible and mixed manner. Molecular docking was carried out to simulate the affinity between compound and α-glucosidase.